Leukoencephalopathy with Brain stem and Spinal cord involvement and Lactate elevation (LBSL): Report of a new family and a novel DARS2 mutation - Wei-Lin Huang; Maija R. Steenari; Rebekah Barrick; Mariella T. Simon; Richard Chang; Shaya S. Eftekharian; Alexander Stover; Philip H. Schwartz; Alexandra Latini; Jose E. Abdenur (Molecular Genetics and Metabolism Reports, 2024)
Background: LBSL is a mitochondrial disorder caused by mutations in the mitochondrial aspartyl-tRNA synthetase gene DARS2, resulting in a distinctive pattern on brain magnetic resonance imaging (MRI) and spectroscopy. Clinical presentation varies from severe infantile to chronic, slowly progressive neuronal deterioration in adolescents or adults. Most individuals with LBSL are compound heterozygous for one splicing defect in an intron 2 mutational hotspot and a second defect that could be a missense, non-sense, or splice site mutation or deletion resulting in decreased expression of the full-length protein. Aim: To present a new family with two affected members with LBSL and report a novel DARS2 mutation. Results: An 8-year-old boy (Patient 1) was referred due to headaches and abnormal MRI, suggestive of LBSL. Genetic testing revealed a previously reported c.492 + 2 T > C mutation in the DARS2 gene. Sanger sequencing uncovered a novel variant c.228-17C > G in the intron 2 hotspot. Family studies found the same genetic changes in an asymptomatic 4-year-old younger brother (Patient 2), who was found on follow-up to have an abnormal MRI. mRNA extracted from patients' fibroblasts showed that the c.228-17C > G mutation caused skipping of exon 3 resulting in lower DARS2 mRNA level. Complete absence of DARS2 protein was also found in both patients. Summary: We present a new family with two children affected with LBSL and describe a novel mutation in the DARS2 intron 2 hotspot. Despite findings of extensive white matter disease in the brain and spine, the proband in this family presented only with headaches, while the younger sibling, who also had extensive white matter changes, was asymptomatic. Our in-vitro results confirmed skipping of exon 3 in patients and family members carrying the intron 2 variant, which is consistent with previous reported mutations in intron 2 hotspots. DARS2 mRNA and protein levels were also reduced in both patients, further supporting the pathogenicity of the novel variant.